PENGARUH KREDIBILITAS INFLUENCER DI MEDIA SOSIAL TERHADAP KEPUTUSAN WISATAWAN MILENIAL KE LABUAN BAJO - Michael Reivin Limengka; N.M.S. Sofia Wijaya; Putu Agus Wikanatha Sagita (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2021)
The study aims at finding out the characteristic of the millennial tourists who visit Labuan Bajo and identifying the influence of the social media influencers’ credibility on their decision to visit Labuan Bajo. In selecting the sample, the study used the purposive sampling method in which some online questionnaires were given to 100 respondents via Google Form feature. The techniques of analyzing the data applied in the study were descriptive qualitative and multiple linear regression analysis using IBM SPSS 25.0 for Windows application. The result of the study shows that, partially and simultaneously, there is a positive impact of the social media influencers’ credibility on the millennial tourists’ decision to visit Labuan Bajo. The results showed that partially, the influencers' credibility positively and significantly affected the millennial tourists’ decision to visit Labuan Bajo. The sig. value of each are as follows: Attractiveness (X1) of 0.043 < 0.05; The Trustworthiness (X2) of 0.047 < 0.05 and the Expertise (X3) of 0.000 < 0.05. While simultaneously, there is a positively and significantly affected the social media Influencers’ credibility on the Millennial tourists’s decision to visit Labuan Bajo, with a sig. value of 0.000 < 0.05.